2019
DOI: 10.1002/hep.30617
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of Macrophage Activation and Immune Danger Signals Predict Clinical Outcomes in Alcoholic Hepatitis

Abstract: Although mortality due to acute alcoholic hepatitis (AH) correlates with Model for End-Stage Liver Disease (MELD) scores, biomarkers are critically needed to manage this disease. Increases in inflammatory markers and macrophage activation are associated with acute AH and could be potential biomarkers of clinical events and/or mortality. We enrolled 89 clinically diagnosed AH patients in four US academic medical centers. Plasma from AH patients had a significant increase in gut microbial translocation indicator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 51 publications
(76 reference statements)
1
51
0
Order By: Relevance
“…Recent studies found that biomarkers such as cytokeratin-18 fragments, soluble cluster of differentiation 14, lipopolysaccharide binding protein (LBP), osteopontin (a multifunctional phosphoprotein involved in neutrophil activation) and circulating levels of macrophage activation sCD163 and sCD206t can indicate severity and predict clinical outcomes in AH helping the management of the disease 54 55…”
Section: Epidemiologymentioning
confidence: 99%
“…Recent studies found that biomarkers such as cytokeratin-18 fragments, soluble cluster of differentiation 14, lipopolysaccharide binding protein (LBP), osteopontin (a multifunctional phosphoprotein involved in neutrophil activation) and circulating levels of macrophage activation sCD163 and sCD206t can indicate severity and predict clinical outcomes in AH helping the management of the disease 54 55…”
Section: Epidemiologymentioning
confidence: 99%
“…Some of the advantages of the MELD score over the DF are the use of INR as compared to prothrombin time, and the use of serum creatinine to include renal function, which plays an important role in the prognosis of AH patients [16]. Several studies have estimated that MELD may be equivalent to or even better than the DF as a prognostic marker of AH [26][27][28].…”
Section: Model Of End-stage Liver Disease (Meld)mentioning
confidence: 99%
“…Surface proteins have numerous functions including acting as a receptor, transport channel, enzyme activity and intracellular identification and interaction. In the liver, CD glycoproteins are mainly detected on Kupffer cells [28]. Some markers like CD163 are also released in response to the bacterial stressors like lipopolysaccharides (LPS), which are detectable in the plasma making this marker relatively easy to measure [71].…”
mentioning
confidence: 99%
“…So far, biomarkers of systemic inflammation and infection have performed fairly well to distinguish patients with a stable disease course from those at higher risk of decompensation [2][3][4]. Moreover, biomarkers of macrophage activation and immune danger signals were demonstrated to predict outcome in patients with decompensated liver cirrhosis, especially in patients with alcoholic hepatitis [5].…”
Section: Introductionmentioning
confidence: 99%
“…OPN levels positively correlated with total bilirubin, Model for End-Stage Liver Disease (MELD) score, MELD-Na score and monocyte count. Moreover, OPN was identified as an independent risk factor for mortality in ACLF and reflected macrophage activation in patients with liver cirrhosis and alcoholic hepatitis [5]. Since many analyses suggested comparable features of different SIBILINGs when tested on their function as a biomarker for a specific disease condition [15], we hypothesized that BSP might also represent a previously unrecognized marker in the context of liver cirrhosis.…”
Section: Introductionmentioning
confidence: 99%